Pemanfaatan Kebun Tanaman Obat untuk Mencegah Penyakit Tidak Menular - Mangunsong, Sonlimar; Pastari, Marta; Sumastri, Heni; Pastati, Taufik Meidiansyah; Mas'ud, Beri; Yani, Tiara; Rahmah, Afifah (Pusat Penelitian dan Pengabdian kepada Masyarakat, Politeknik Kesehatatan Kemenkes Palembang, 2024)
Herbal plants are plants that have been identified and known based on human observations to have compounds that are useful for preventing, curing disease, carrying out certain biological functions, and preventing insect and fungal attacks (Sapitri et al., 2022). With the many benefits that can be obtained from herbal plants, using your yard as a place to grow herbal plants will bring many benefits, especially for rural communities. Herbal plants do not require large areas of land, so planting them will make their cultivation very easy. The community will have plants that can be used to prevent and treat various diseases. So, people can avoid excessive use of chemical drugs (Pantur et al., 2022). The problem solutions offered in this community service activity are in the form of; a) Focus Group Discussion (FGD) I and II; explanation of program and technical activities with related parties (Pangkalan Benteng Village Government, Pangkalan Benteng Village Health Center and Poskesdes Officers, Pangkalan Benteng Village Posyandu Cadres, Community Leaders), b) Implementation of Activities; Socialization, Education and Assistance in Planting Herbal Plants and Their Use to Improve the Health and Economy of the Pangkalan Benteng Village Community for the Community and Health Cadres; Launching Examples of Herbal Plants (Family Medicinal Plants) planted in the grounds of the Pangkalan Benteng Village Office, c) Monitoring Evaluation; strengthening the sustainability of the program with the assistance of health cadres so that the activity objectives will be achieved (100% of the people of Pangkalan Benteng Village have herbal plants (family medicinal plants) in their respective yards and superior products emerge for the family economic ranking; information obtained through WAG with health cadres. Based on the achievement targets and activity results, it can be concluded that after the intervention was given, the results of the activities showed that; 80% of the people of Pangkalan Benteng Village who did not have herbal plants (family medicinal plants) in their yards, stated that they would start planting according to the information obtained from this activity; 100% of the people of Pangkalan Benteng Village already know how to optimize the benefits of herbal plants to improve the health status and economy of the family (100% of the family's superior herbal products have been educated and assisted regarding the use and processing of herbal plants (medicinal plants); family). As a follow-up to this activity, health cadres will accompany all heads of families in stages to plant herbal plants (family medicinal plants) in their respective yards and form small and medium enterprises (MSMEs) to make superior herbal products for the people of Pangkalan Benteng Village to improve the economy. family.